2015
DOI: 10.1016/j.jad.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Faith-adapted psychological therapies for depression and anxiety: Systematic review and meta-analysis

Abstract: Background Incorporating faith (religious or spiritual) perspectives into psychological treatments has attracted significant interest in recent years. However, previous suggestion that good psychiatric care should include spiritual components has provoked controversy. To try to address ongoing uncertainty in this field we present a systematic review and metaanalysis to assess the efficacy of faith-based adaptations of bona fide psychological therapies for depression or anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 49 publications
2
60
0
4
Order By: Relevance
“…4. Finally, data from outcome research studies have supported the idea that spiritual and religious approaches to treatment have been effective in treating many psychosocial issues (Anderson, Heywood-Everett, Siddiqi, Wright, Meredith, & McMillan, 2015;Hook, Worthington, Davis, Jennings, Gartner, & Hook, 2010;McCullough, 1999;Smith, Bartz, & Richards, 2007;Worthington, Hook, Davis, & McDaniel, 2011;Worthington, Kurusu, McCullough, & Sandage, 1996;Worthington & Sandage, 2001). …”
Section: General Trends In the Literature On Integrating Spiritualitymentioning
confidence: 97%
See 1 more Smart Citation
“…4. Finally, data from outcome research studies have supported the idea that spiritual and religious approaches to treatment have been effective in treating many psychosocial issues (Anderson, Heywood-Everett, Siddiqi, Wright, Meredith, & McMillan, 2015;Hook, Worthington, Davis, Jennings, Gartner, & Hook, 2010;McCullough, 1999;Smith, Bartz, & Richards, 2007;Worthington, Hook, Davis, & McDaniel, 2011;Worthington, Kurusu, McCullough, & Sandage, 1996;Worthington & Sandage, 2001). …”
Section: General Trends In the Literature On Integrating Spiritualitymentioning
confidence: 97%
“…Studies clearly demonstrate that religiously oriented therapies have a positive impact in the treatment of religiously observant clients when treatment goals are framed within their spiritual context (Anderson et al, 2015;Hook et al, 2010;Martinez, Smith, & Barlow, 2007;Worthington, Hook, Davis, & McDaniel, 2011).…”
Section: General Trends In the Literature On Integrating Spiritualitymentioning
confidence: 99%
“…Results of a meta-analysis indicated that spirituality and religiosity has a positive effect on psychological outcomes in adolescents and emerging adults (Yonker et al 2012). Further, attending religious services has been found to be a protective factor against suicide (Anderson et al 2015).…”
Section: Religiosity and Adolescent Depressionmentioning
confidence: 99%
“…Estas mantêm os componentes básicos das abordagens seculares, e fazem modificações para acomodar espiritualidade e religiosidade (Hook et al 2013). Em uma revisão sistemática e metanálise, Anderson et al (2015) tentaram estabelecer se a terapia comportamental cognitiva (tcc) adaptada à fé seria mais eficaz que a tcc padrão, ou grupos de controle, para tratar pacientes com depressão e ansiedade. Os métodos utilizados para integrar a fé aos tratamentos tradicionais foram uma combinação de discussão de ensinamentos religiosos e das escrituras para contestar crenças irracionais ou dar suporte para mudança cognitiva ou comportamental; utilizar estratégias de enfrentamento religioso, como ensinamentos das escrituras para lidar com sentimentos como medo, culpa, vergonha, desespero, raiva; promoção de sistemas de crenças e valores que trazem ajuda, ou o uso de valores compartilhados para fortalecer a relação terapêutica; incorporar práticas religiosas como a oração.…”
Section: Psicoterapias Adaptadas à Féunclassified